Facilitators and barriers to the clinical application of teamwork skills taught in multidisciplinary simulated Trauma Team Training. Issue 5 (May 2019) - Murphy, Margaret; Curtis, Kate; McCloughen, Andrea
Abstract: Background: Efforts to improve teamwork in trauma include simulation-based team training with a non-technical skills (NTS) focus. However, there is a lack of evidence to inform the development of team training programs for maximum uptake of NTS in clinical practice. This descriptive paper aims to evaluate the extent NTS were practiced by the trauma team in a Level 1 trauma hospital after NTS training and to identify facilitators and barriers to use of NTS in clinical practice. Method: A 38-item questionnaire targeting clinicians who attended a simulation based multidisciplinary Trauma Team Training program was developed. The questionnaire was developed using the Theoretical Domains Framework, a validated tool to identify what practices need to change. It included questions on the current practice of NTS in real life trauma resuscitation. Results: Eighty six of 235 eligible participants (rate 37%) responded to the questionnaire. All relevant professions and clinical services were represented. There were 15 facilitators and 12 barriers identified. Barriers and facilitators were allocated to categories of factors known to influence trauma team practices. These were: (1) organisational factors that influence the trauma team, (2) team factors that influence teamwork and (3) cognitive factors that influence team decision making. Conclusion: NTS were being used by frontline clinicians in real world trauma resuscitations to varying degrees, depending on organisational, team and cognitive facilitators and barriers. Facilitators to the implementation of NTS skills during trauma emergencies included team composition, roles and responsibilities, procedural compliance and leadership. Barriers included decision making and communication. This study described team members experience of using NTS in 'real world trauma resuscitation' to inform future team training interventions.